Obesity and susceptibility to autoimmune diseases. (May 2011) - Procaccini, Claudio; Carbone, Fortunata; Galgani, Mario; La Rocca, Claudia; De Rosa, Veronica; Cassano, Silvana; Matarese, Giuseppe
For decades, obesity has been considered to be the result of the complex interaction between genes and the environment and its pathogenesis is still unresolved. The discovery of hormones and neural mediators responsible for the control of food intake and metabolism at the hypothalamic level has provided fundamental insights into the complicated pathways that control food intake. However, the molecular basis for the association between obesity and low-degree chronic inflammation is still unknown. More recently, the discovery of leptin, one of the most abundant adipocyte-derived hormones, has suggested that nutritional status, through leptin secretion, can control immune self-tolerance modulating Treg suppressive function and responsiveness. Furthermore, recent experimental evidence has shown the presence of an abundant adipose tissue-resident Treg population responsible for the control of metabolic parameters and glucose homeostasis. Better knowledge of the intricate network of interactions among leptin-related energy regulation, Treg activities and obesity could lead to valuable strategies for therapeutic intervention in obesity and obesity-associated insulin resistance.